The anatomy of sovereign risk contagion - Wu, Eliza; Erdem, Magdalena; Kalotychou, Elena; Remolona, Eli (My University, 2016)
© 2016 Elsevier Ltd The channels for the cross-border propagation of sovereign risk in the international sovereign debt market are analysed. Identifying sovereign credit events as extraordinary jumps in CDS spreads, we distinguish between the immediate effects of such events and their longer term spillover effects. To analyse “fast and furious” contagion, we use daily CDS data to conduct event studies around a total of 89 identified credit events in a global country sample. To analyse “slow-burn” spillover effects, we apply a multifactor risk model, distinguishing between global and regional risk factors. We find that “fast and furious” contagion has been primarily a regional phenomenon, whilst “slow-burn” spillover effects can often be global in scope, especially those of the recent European debt crisis. The global risk factors are found to be driven by investor risk appetites and debt levels, whilst the regional factors depend on economic fundamentals of countries within a region.
Keywords: Sovereign risk; Contagion; Credit default swap; Credit event; Debt crisis; Spillover